2021
DOI: 10.35772/ghm.2021.01068
|View full text |Cite
|
Sign up to set email alerts
|

International cooperation on health and medical care for viral hepatitis: 30 years of activities on comprehensive viral hepatitis control of the JICA group training program for developing countries

Abstract: The National Hospital Organization Kumamoto Medical Center has conducted a group training course for health care workers (HCW) from developing countries on viral hepatitis and its related diseases in cooperation with the Japan International Cooperation Agency, for 30 years. In the first 10 years, the course included acquired immunodeficiency syndrome (AIDS), adult T-cell leukemia/lymphoma (ATL), and hepatitis. Following the discovery of the hepatitis C virus and the genotype of the hepatitis B virus, and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In contrast to online trainings, an in-depth review of the primary curriculum for each identified workshop was not possible. Published data on certain workshops trainings [ 26 , 47 , 49 56 ] indicate that the curricula were generally comprehensive, covering epidemiology, diagnosis, workup, and treatment of HBV, HCV, or both. We highlight two specific trainings, the WHO Southeast Asia and Western Pacific regional training [ 57 ] and the Institute of Liver and Biliary Sciences “Hepatitis Induction Program” for nurses [ 58 ] Tables 5 , 6 , 7 , 8 and 9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to online trainings, an in-depth review of the primary curriculum for each identified workshop was not possible. Published data on certain workshops trainings [ 26 , 47 , 49 56 ] indicate that the curricula were generally comprehensive, covering epidemiology, diagnosis, workup, and treatment of HBV, HCV, or both. We highlight two specific trainings, the WHO Southeast Asia and Western Pacific regional training [ 57 ] and the Institute of Liver and Biliary Sciences “Hepatitis Induction Program” for nurses [ 58 ] Tables 5 , 6 , 7 , 8 and 9 .…”
Section: Resultsmentioning
confidence: 99%
“…In comparison to online trainings, there has been more published evaluations of viral hepatitis workshop trainings, both based on programme metrics for blended learning programmes reported above and published reports from workshops and educational initiatives in countries including Rwanda, Myanmar, Mongolia, Egypt, Iran, and Tanzania [ 26 , 47 , 49 , 53 – 56 , 62 , 63 ] (Tables 8 and 9 ).…”
Section: Resultsmentioning
confidence: 99%